2005
DOI: 10.2307/3583416
|View full text |Cite
|
Sign up to set email alerts
|

Are Process Indicators Adequate to Assess Essential Obstetric Care at District Level?: A Case Study from Rufiji District, Tanzania

Abstract: To assess coverage and quality of essential obstetric care (EOC) and the appropriateness of using process indicators, a 3-month follow-up study was done in Rufiji district, Tanzania, involving 2 hospitals, 4 health centres, 10 large dispensaries and 10 randomly selected small dispensaries. Data collection was done on process indicators as suggested by UNICEF/ WHO/UNFPA (UN) and 'unmet obstetric need (UON) for major obstetric intervention (MOI)'. With standard values in (brackets), the district had two comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…This is in accordance with other studies in developing countries where geographical and financial difficulties deter women from going for the referral [8,20,23,24]. We found that many women referred due to prenatal and natal complications were able to mobilize resources and went to hospital.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with other studies in developing countries where geographical and financial difficulties deter women from going for the referral [8,20,23,24]. We found that many women referred due to prenatal and natal complications were able to mobilize resources and went to hospital.…”
Section: Discussionsupporting
confidence: 92%
“…Lack of providers’ ability to screen, counsel and inform women on danger signs seen in rural Tanzania may be present on our area, too. Other threats to improved care are lack of transport, financial constraints, poor compliance with referral, and lack of birth preparedness [27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, as in most low-income countries, women with high-risk pregnancy and complications are referred to higher level facilities in accordance with the guidelines [3]. Despite the provision of referral advice in the lower level facilities, a substantial number of women do not reach the referral hospitals [47] and only 64% are delivered by a skilled birth attendant [8]. The Three Delay Model by Thaddeus and Maine [9] illustrates studies investigating barriers to adherence to referral advice for hospital delivery in rural Tanzania, including financial constraints, difficulty in accessing transport, poor quality of care and shortage of staff [5,10–12].…”
Section: Introductionmentioning
confidence: 99%